The Model of the Criminological Characteristics of the Subject of Crimes in the Field of Taxation - SHANAZAROVA, Elena V.; VOLODIN, Dmitry A.; . ZYKOV, Daniil A; MIKHALEVA, Olga V.; SAVIN, Andrei A. (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the analysis of the personality characteristics of persons who commit crimes in the field of taxation, as well as empirical forensic material in the current forensic paradigm of research, in order to develop a stable criminological portrait of tax criminals. A comprehensive theoretical formation of the personality structure of tax criminals is carried out taking into account the number of determinants: socio-demographic, penal, moral and psychological levels, attention is paid to the functional purpose of the doctrine of personality. The article gives a reasoned empirical criticism to the position on the delimitation of the general characteristics of the objective side of the act depending on the characteristics of the subject of a specific crime. That is, depending on the organizational and legal forms of organizations, the official of which is or was the person who committed the crime, on the position held by him. We draw attention to the correlation of quantitative and qualitative indicators of the level of education of tax criminals and their distribution by percentage in the general structure of such crime. The practical relevance and consistency of the theoretical thesis on the existence of a correlation between the level of education of subjects of tax crimes and the frequency of their commission is indirectly confirmed.